New thilinear hybrid of hard yellow corn for the Peruvian tropic - Díaz-Chuquizuta, Percy (2022)
Introduction. Hard yellow corn (Zea mays L.) is the main source for food processing; therefore, it is necessary to generate hybrids with yields higher than 2.8 t ha-1 and climatic adaptability. Objective. To evaluate and compare the agronomic behavior of five experimental trilinear hybrids of hard yellow corn  maize and the Marginal 28T variety in eight tropical Peruvian locations. Materials and methods. The experiment took place in two phases: from March 2018 to March 2019 in four validation plots in San Martin, and from March to December 2019 in four adaptabilities plots in San Martín, Pucallpa, Loreto, and Amazonas. The evaluated variables were: plant and ear height, size and weight of ear, roots lodging, rust resistance, and yield (t ha-1). A randomized complete block design was applied, with a combined analysis of yield genotype x environment interaction with the additive main effects and multiplicative interaction models. Results. The hybrid HTE6 had the highest ear diameter (4.66 cm), ear weight (190, 76 g), number of rows per ear (14.26), grains per row (37.45), total grain weight (156.21 g), and grain yield (7.21 t ha-1). HTE6 showed superior adaptability in Iquitos (9.2 t ha-1) and San Martín (8.1 t ha-1). In the genotype-environmental interaction, it reached 7.18 t ha-1, with the highest stability in the eight localities. Conclusion. Among the five trilinear hybrids and the Marginal 28T variety, the HTE6 had the best agronomic performance and the highest yield in the eight evaluated locations. Thus, it is considered the more suitable trilinear hybrid for the tropical conditions of Peru.